Catheter treatment of tachyarrhythmias in children under 5 years old using thermal mapping and discrete applications - M. Meshkova; A. Doronin; V. Khanenova; D. Zabashta; N. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2019)
Radiofrequency catheter ablation (RCA) for the treatment of tachyarrhythmias in children under the age 5 years is not used as often as in patients of other age groups. The RCA procedure has great advantages over chronic antiarrhythmic therapy, but its use in young children is limited due to specific complications.The objective is to analyse our own experience in catheter treatment for tachyarrhythmias in children under the age of 5 years using the method of thermoal mapping and discrete applications.Material and methods. The article presents the results of 68 RCA in 56 consecutive patients under the age of 5 years old, who underwent surgical interventions from 2007 to 2017. Ablations of accessory pathways were more frequent among the procedures. There were 12 (17.9%) reoperations. The immediate efficacy of RFA was 88.0%, after reoperations – 96.0%. 5 (7.3%) complications were reported, of which 2 (2.9%) were significant. There was no mortality.RCA was carried out by one or two 6F (with a body weight of up to 15 kg) or 7F non-irrigated catheters with a 4-mm distal pole. The parameters of applications did not exceed 53°С, 35 W, 40 s. After 2011, the applications were applied discretely at (45 °C →48 °C →50 °C →53 °C) and after thermal mapping.Results and discussion. After the introduction of clear indications to RCA in young children in 2011, despite an annual increase in the number of children with tachyarrhythmia treated in our clinic, the percentage of ablation performed at early age decreased.Since 2012, ablations were performed in older children with a greater body weight. At the same time, despite the greater number of RCA in children younger than 5 years old during this period, there were no complications, and the success of procedures increased from 85% to 91%.We associate the growth of RCA direct success with the fact that we were able to avoid urgent procedures and procedures in decompensated patients.A new treatment protocol and less aggressive, well-defined indications for RCA in children under the age 5 years have allowed us to reduce the number of ablation at earlier age when the probability of complications is greatest.The ‘gentle’ RCA method allows us to make sure that the application in the selected place was safe, and in case of adverse effects – to immediately stop it without irreversible consequences. The advantages of this technique are confirmed by the absence of complications associated with RCA after the new method implementation.Since 2012 we have had a higher percentage of reoperations (up to 18%), but all of them were performed at older age. We consider this to be justified in the absence of complications and high efficacy of RCA.